Characterization, Biomarkers, and Reversibility of a Monoclonal Antibody-induced Immune Complex Disease in Cynomolgus Monkeys (Macaca fascicularis). (June 2014) - Heyen, Jonathan R.; Rojko, Jennifer; Evans, Mark; Brown, Tom P.; Bobrowski, Walter F.; Vitsky, Allison; Dalton, Shana; Tripathi, Niraj; Bollini, Sangeetha Subbarao; Johnson, Theodore; Lin, John C.; Khan, Nasir; et al.
Two 6-month repeat-dose toxicity studies in cynomolgus monkeys illustrated immune complex–mediated adverse findings in individual monkeys and identified parameters that potentially signal the onset of immune complex–mediated reactions following administration of RN6G, a monoclonal antibody (mAb). In the first study, 3 monkeys exhibited nondose-dependent severe clinical signs accompanied by decreased erythrocytes with increased reticulocytes, neutrophilia, monocytosis, thrombocytopenia, coagulopathy, decreased albumin, azotemia, and increased serum levels of activated complement products, prompting unscheduled euthanasia. Histologically, immunohistochemical localization of RN6G was associated with monkey immunoglobulin and complement components in glomeruli and other tissues, attributable to immune complex disease (ICD). All 3 animals also had anti-RN6G antibodies and decreased plasma levels of RN6G. Subsequently, an investigational study was designed and conducted with regulatory agency input to detect early onset of ICD and assess reversibility to support further clinical development. Dosing of individual animals ceased when biomarkers of ICD indicated adverse findings. Of the 12 monkeys, 1 developed anti-RN6G antibodies and decreased RN6G exposure that preceded elevations in complement products, interleukin-6, and coagulation parameters and decreases in albumin and fibrinogen. All findings in this monkey, except for antidrug antibody (ADA), reversed after cessation of dosing without progressing to adverse sequelae typically associated with ICD.